Coumarin and Safrole Content in Cinnamon-Flavored Food Products on the Syrian Market - Raw'aa Solaiman ,; Joumaa Al-Zehouri, (Journal of Pharmacy and Nutrition Sciences, 2017)
Some plants that are processed into foods often contain natural substances that may be hazardous to human health. One example is coumarin, which is known to cause liver and kidney damage in rats, mice and probably humans. Coumarin is found in different Cinnamomum species such as Cinnamomum cassia, Cinnamomum loureiroi, and Cinnamomum burmannii; all commonly referred to as cassia. Another hazardous substance is Safrole. Safrole is reasonably anticipated to be a human carcinogen based on sufficient evidence of carcinogenicity from studies in experimental animals; and is mainly present in cinnamon leaf oil and could be a possible contaminant in cinnamon powder. European Council’s Directive on food flavourings 88/388/EEC limits safrole in foodstuffs to 1ppm. The content of coumarin is regulated in the European Regulation (EC) No 1334/2008. In the present study, coumarin and safrole levels were analyzed in locally bought cinnamon samples and cinnamon-flavored food products using a validated HPLC method with diode array detector (DAD). Appreciable amounts of coumarin were found in bakery products with concentrations up to 39.466 mg/kg in certain kinds of cookies, whereas safrole was undetectable. Our exposure data on coumarin in bakery products show that there is still a need for a continued regulation of coumarin in foods. A toxicological re-evaluation of coumarin with the aim to derive scientifically founded maximum limits should be conducted with priority.